Isolation and Preparation Three Types of Antigens From S.pseudintermedius: Isolasi dan Persiapan Tiga Jenis Antigen dari S. pseudintermedius. - Mustafa Fadhil Latif; Murtada Fadhil Latif (Academia Open, 2023)
This study aimed to prepare and evaluate the immunogenic activity of three distinct antigens derived from S. pseudintermedius, a prominent isolate identified from otitis externa samples of dogs and human infections. The isolation and identification of Staphylococcus species were conducted using rigorous cultural, morphological, and biochemical methods, with confirmation via VITEK technique. A total of 100 samples, comprising 50 from humans and 50 from dogs, were collected. Following successful antigen preparation, twenty rabbits were immunized and divided into four groups, including a control group. Cellular immunity was assessed through a delayed hypersensitivity (DTH) skin test, revealing positive skin reactions among the immunized groups. Subsequent challenge dosing resulted in clinical observation, with marked signs of illness and severe infection in the control group. Histopathological examination further confirmed this infection and bacterial isolation. Remarkably, the prepared antigens exhibited substantial protein concentrations and induced a robust immune response in immunized rabbits against experimental L. monocytogenes infection. These findings underscore the potential of S. pseudintermedius antigens for developing protective strategies against bacterial infections in both veterinary and human medicine, offering significant implications for global health practitioners and researchers in the field. Highlights : Rigorous identification: S. pseudintermedius derived antigens evaluated after precise Staphylococcus species identification using cultural, morphological, and biochemical methods, confirmed via VITEK technique. Robust immune response: Immunization with prepared antigens induced positive delayed hypersensitivity skin reactions and protected against severe L. monocytogenes infection, demonstrating potential for cross-species bacterial infection prevention. Clinical and histopathological insights: Control group exhibited illness and Listeriosis upon challenge, validated through histopathological examination, highlighting antigen-induced protection against bacterial invasion.